2021
DOI: 10.1111/jocn.16017
|View full text |Cite
|
Sign up to set email alerts
|

Infrared augmented reality device versus standard procedure for peripheral venous catheterisation in children less than 3 years old: A quasi‐experimental cluster randomised controlled trial

Abstract: Aim and objective The objective of this study was to evaluate the AccuVeinAV400® viewing device for peripheral venous catheter insertion in children on the first try. Background Inserting a peripheral venous catheter is the most frequent invasive procedure carried out by healthcare professionals in hospitalised children. Several attempts are sometimes necessary, and veins can be damaged. Design A quasi‐experimental cluster randomised controlled trial based on the CONSORT 2010 guidelines. Methods This randomise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In pediatric patients, most studies found no significant improvement in first-attempt success of intravenous cannulation, number of attempts, or the amount of time or pain when using an NIR imaging device for vein visualization. 8,9 The training of medical and nursing students concerning venipuncture usually does not follow a systematic scheme. 10 Some approaches to improve these teaching techniques include theoretical lectures, e-learning courses, video lessons, and practical exercises with a manikin or haptic devices, as well as with simulation-based training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pediatric patients, most studies found no significant improvement in first-attempt success of intravenous cannulation, number of attempts, or the amount of time or pain when using an NIR imaging device for vein visualization. 8,9 The training of medical and nursing students concerning venipuncture usually does not follow a systematic scheme. 10 Some approaches to improve these teaching techniques include theoretical lectures, e-learning courses, video lessons, and practical exercises with a manikin or haptic devices, as well as with simulation-based training.…”
Section: Discussionmentioning
confidence: 99%
“…Its simple, cheap, noninvasive, and quick applicability is especially highlighted by some authors. In pediatric patients, most studies found no significant improvement in first-attempt success of intravenous cannulation, number of attempts, or the amount of time or pain when using an NIR imaging device for vein visualization 8,9…”
Section: Discussionmentioning
confidence: 99%
“…Due to increased body fat and patterns of distribution, IV placement is challenging in the younger pediatric population [7]. Though age [1,8] is a known risk factor for difficult IV access and a predictive factor included in the difficult intravenous access (DIVA) score [8,9], few studies have focused on the use of this device exclusively in infant and toddler populations [2,8]. The primary objective of our study was to compare the efficacy of an IR vein visualization device with the standard cannulation technique (i.e., no IR device) in children (age < 2 years) presenting for elective magnetic resonance imaging (MRI) procedures under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…It leads to more attempts to establish the PIVC and cause the vein damage. 1,2 Previous randomized studies done with PIVC mentioned first time success rates ranging from 44% to 53% and required second or third attempts for successful PIVC insertion in pediatric patients. 3,4 Therefore, the PIVC on the pediatric patients was a challenging task for the healthcare professionals in the clinical care and practice.…”
Section: Introductionmentioning
confidence: 99%